Tahlîlu At-Tarâkîb An-Nahwîyah Al-Ghâmidah 'inda Risâlati Tullâbi Al-Mâjistîr Min Qismi Ta'lîmi Al-Lughah Al-'Arâbîyah Fî Jâmi'ah Surakarta Al-Islâmîyah Al-Hukûmîyah wa Kasyfu Al-Ma'âni Al-Haqîqîyah min hâ bi Istikhdâmi Al-Qarâin. - Hanif Mantiq Riyadi; Maslamah (Rayah Al-Islam, 2022)
أهداف هذا البحث لتحليل الغموض في التراكيب النحوية التي تحتويها رسائل طلاب الماجستير من قسم تعليم اللغة العربية في جامعة سوراكرتا الإسلامية الحكومية. ولكشف المعنى الحقيقي أو المطلوب من الغموض الموجود باستعمال القرينة. هذا بحث وصفي نوعي بأسلوب تحليل المحتوى. وموضوعه رسالتان لطلاب ماجستير من قسم تعليم اللغة العربية بجامعة سوراكرتا الإسلامية الحكومية. جُمعت البيانات من هذا البحث بطريقة تحليل الوثائق. يقام التحليل بكتابة البيانات، ثم تنظيمها، وتصنيفها، وتسجيلها ثم تحديد الأنساق والأنماط، فالتحقق من النتائج. وأما نتائج البحث فتشير إلى: أن عدد التراكيب النحوية الغامضة في الرسالتين الاثنتين 19 تركيبا، وهي: 5 تراكيب في الغموض في المصدر (المصدر المضاف)، تركيبان في الغموض في الجار والمجرور، 9 تراكيب في الغموض في الموصوف والصفة المنسوبة، تركيب واحد في الغموض في التركيب العطفي، تركيبان في الغموض في العطف ب"أو". ولكشف المعاني الحقيقية منها ثلاث قرائن فقط قابلة للاستخدام من القرائن العشرة الموجودة التي عرضها الدكتور فاضل صالح السامرائي، والقرائن المستخدمة هي: القرينة اللفظية (12 مرة) وقرينة السياق (3 مرات) والقرينة العلمية (4 مرات). This study aims to Analyze of the ambiguity of the grammatical structure contained in the theses of master students majoring in Arabic Language Education at the State Islamic University of Surakarta. And to reveal the true or desired meaning of the existing ambiguity by using qarinah. This research is a qualitative descriptive study using the document analysis method. The object of the analysis is the two master's theses students of the Department of Arabic Language Education at the Surakarta State Islamic University. In this study the data were collected by document analysis method. Analysis was done by writing data, then organizing it, classifying it, recording it then identifying patterns, thereupon verifying the results. The results showed that there were 19 grammatical structures that had ambiguous meanings in the three theses, they are: ambiguity in adjunctive masdar: 5, ambiguity in prepositional phrases: 2, ambiguity in adjective phrases with relative isim: 9, ambiguity in the coordinating structure: 1, ambiguity in the coordination structure with preferred relationship markers: 2. And to reveal the true meaning of these grammatical structures, only three can be used from the ten existing qarinah presented by Dr. Fadel Salih al-Samarrai, as for the qarinah used are: qarinah lafdziyyah (12 times), qarinah siyaq (3 times), qarinah ilmiyyah (4 times).